Predicting the Emergence of Major Neurocognitive Disorder Within Three Months After a Stroke - Aamodt, Eva Birgitte; Schellhorn, Till; Stage, Edwin; Sanjay, Apoorva Bharthur; Logan, Paige E.; Svaldi, Diana Otero; Apostolova, Liana G.; Saltvedt, Ingvild; Beyer, Mona Kristiansen (Frontiers in Aging Neuroscience, 2021)
Background: Neurocognitive disorder (NCD) is common after stroke, with major NCD appearing in about 10% of survivors of a first-ever stroke. We aimed to classify clinical- and imaging factors related to rapid development of major NCD three months after a stroke, so as to examine the optimal composition of factors for predicting rapid development of the disorder. We hypothesized that the prediction would mainly be driven by neurodegenerative as opposed to vascular brain changes. Methods: Stroke survivors from five Norwegian hospitals were included from the ‘Norwegian COgnitive Impairment After STroke’ (Nor-COAST) study. A support vector machine (SVM) classifier was trained to distinguish between patients who developed major NCD three months after the stroke and those who did not. Potential predictor factors were based on previous literature and included both vascular and neurodegenerative factors from clinical and structural magnetic resonance imaging (MRI) findings. Cortical thickness was obtained via FreeSurfer segmentations, and volumes of white matter hyperintensities (WMH) and stroke lesions were semi-automatically gathered using FSL BIANCA and ITK-SNAP, respectively. The predictive value of the classifier was measured, compared between classifier models and cross-validated. Results: Findings from 227 stroke survivors (age = 71.7 (11.3), males = (56.4%), stroke severity NIHSS = 3.8 (4.8)) were included. The best predictive accuracy (AUC = .876) was achieved by an SVM classifier with 19 features. The model with the fewest number of features that achieved statistically comparable accuracy (AUC = .850) was the 8-feature model. These features ranked by their weighting were; stroke lesion volume, WMH volume, left occipital and temporal cortical thickness, right cingulate cortical thickness, stroke severity (NIHSS), antiplatelet medication intake, and education. Conclusions: The rapid (<3 mo) development of major NCD after stroke is possible to predict with an 87.6% accuracy and seems dependent on both neurodegenerative and vascular factors, as well as aspects of the stroke itself. In contrast to previous literature, we also found that vascular changes are more important than neurodegenerative ones. Although possible to predict with relatively high accuracy, our findings indicate that the development of rapid onset post-stroke NCD may be more complex than earlier suggested.